Maternal weight trajectories and associations with infant growth in South African women - Hlengiwe P. Madlala; Angela M. Bengtson; Luke Hannan; Thokozile R. Malaba; Emma Kalk; Dorothy Nyemba; Andrew Boulle; Landon Myer (BMC, 2023)
Abstract Background Despite the close relationship between pre-pregnancy body mass index (BMI), gestational weight gain (GWG) and postpartum weight (PPW), these factors are often studied separately. There are no data characterising longitudinal weight trajectories among pregnant and postpartum women in urban African populations. We examined maternal weight trajectories from pregnancy through to 12 months postpartum, factors associated with higher weight trajectory class membership and associations of weight trajectories with infant growth at 12 months. Methods Data from 989 women were examined for weight trajectories from first antenatal care visit in pregnancy to 12 months postpartum using latent-class growth models. Baseline factors associated with class membership were assessed using multinomial logistic regression. Of the enrolled women, 613 of their infants were assessed for growth at 12 months. Anthropometry measurements for mothers and infants were conducted by a trained study nurse. Associations between maternal weight trajectory class and infant weight-for-age (WAZ), length-for-age (LAZ), weight-for-length (WLZ) at 12 months of age were analysed using linear regression. Results Four distinct classes of maternal weight trajectories were identified. The classes included consistent low (29%), consistent medium (37%), medium-high (24%) and consistent high (10%) trajectories. Similar to trends observed with medium-high trajectory, baseline factors positively associated with consistent high class membership included age (OR 1.05, 95% CI 1.01-1.09), pre-pregnancy BMI (OR 2.24, 95% CI 1.97-2.56), stage 1 hypertension (OR 3.28, 95% CI 1.68-6.41), haemoglobin levels (OR 1.39, 95% CI 1.11-1.74) and parity (OR 1.39, 95% CI 1.15-1.67); living with HIV (OR 0.47, 95% CI 0.30-0.74) was inversely associated. In adjusted analyses, compared to consistent medium weight trajectory, consistent low weight trajectory (mean difference -0.41, 95% CI -0.71;-0.12) was associated with decreased, and consistent high weight trajectory (mean difference 1.21, 95% CI 0.59-1.83) with increased infant WAZ at 12 months of age. Conclusion Identification of unique longitudinal weight trajectory groupings might inform comprehensive efforts targeted at improving healthy maternal weight and infant outcomes.